Kewenangan Majelis Pengawas Notaris Terhadap Notaris yang Terbukti Membuat Akta Secara Berpihak - Rana Dewanty Jusuf; Kurnia Sukmasari (Program Studi Kenotariatan Fakultas Hukum Universitas Pelita Harapan, 2023)
Notary who is appointed directly by the Minister as a public official, is authorized in making authentic deed. In carrying out their positions, Notaries are subject to UUJN and the Notary’s Code of Ethics, and their supervision is carried out by the Notary Supervisory Council. Notaries are required to behave neutrally or impartially in making the deed, but in reality this is still found by the Notary Supervisory Council. By making a deed not impartially before a Notary, it can cause harm to other parties. Therefore, the purpose of this study is to find out the authority of the Notary Supervisory Council against Notaries who are proven to have taken partisan action and how the Notary's responsibility to the injured party is. The research method used is normative research. The authority of the Notary Supervisory Council against a Notary who is proven to have taken a unilateral action is regulated in Article 73 of the UUJN and Article 24-27 of the Permenkumham No. 16 Year 2021, which in this study imposes sanctions in the form of a written warning and the Notary's responsibility to the aggrieved party is from the administrative side, civil liability and criminal liability if it can be proven that a criminal act has been committed. Bahasa Indonesia Abstrak: Notaris diangkat langsung oleh Menteri sebagai pejabat umum, berwenang dalam hal pembuatan akta autentik. Dalam menjalankan jabatannya, Notaris tunduk pada UUJN dan Kode Etik Notaris, serta pengawasannya dilakukan oleh Majelis Pengawas Notaris. Notaris wajib berperilaku netral atau tidak berpihak dalam pembuatan akta, tetapi pada kenyataannya hal tersebut tetap ditemukan oleh Majelis Pengawas Notaris. Dibuatnya akta secara berpihak di hadapan Notaris dapat menimbulkan kerugian bagi pihak lain. Oleh karena itu tujuan penelitian ini untuk mengetahui bagaimana kewenangan Majelis Pengawas Notaris terhadap Notaris yang terbukti membuat akta secara berpihak dan bagaimana tanggung jawab Notaris terhadap pihak yang dirugikan. Metode penelitian yang digunakan adalah penelitian yuridis normatif. Kewenangan yang dimiliki Majelis Pengawas Notaris terhadap Notaris yang terbukti membuat akta secara berpihak diatur dalam Pasal 73 UUJN dan Pasal 24–27 Permenkumham No. 16 Tahun 2021, yang dalam penelitian ini penjatuhan sanksinya berupa teguran secara tertulis dan tanggung jawab Notaris terhadap pihak yang dirugikan adalah dari sisi administratif, tanggung jawab perdata dan tanggung jawab pidana apabila dapat dibuktikan adanya unsur tindak pidana.